2015
DOI: 10.1111/apha.12518
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinylations of albumin decreased binding capacity of hydrophobic metabolites

Abstract: We used a mass spectrometry-based method for the characterization of post-translational modification and demonstrated the pathophysiological impact of a representative post-translational modification of plasma albumin. The data described in this study may help to elucidate the pathophysiological role of protein modifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 37 publications
(65 reference statements)
0
52
0
Order By: Relevance
“…New information presented by Rueth et al . in the current issue of Acta Physiologica extends our knowledge regarding decreased binding capacity of albumin of hydrophobic metabolites especially in uraemic patients. The authors were able to use recent developments in selectivity and sensitivity in mass spectrometry to identify and quantify endogenous post‐translational modifications of albumin.…”
mentioning
confidence: 74%
See 4 more Smart Citations
“…New information presented by Rueth et al . in the current issue of Acta Physiologica extends our knowledge regarding decreased binding capacity of albumin of hydrophobic metabolites especially in uraemic patients. The authors were able to use recent developments in selectivity and sensitivity in mass spectrometry to identify and quantify endogenous post‐translational modifications of albumin.…”
mentioning
confidence: 74%
“…The study by Rueth et al . builds on the previous studies, and it showed that the alteration of albumin in CKD patients had a strong impact on total specific and unspecific binding. Thereby, the number of hydrophobic binding sites carrying indoxyl sulphate and especially tryptophan were significantly decreased.…”
mentioning
confidence: 85%
See 3 more Smart Citations